PERAN SOSIOLOGI PENDIDIKAN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH : The role of educational sociology in forming the character of students at school - Keysha Alea Amanah Fatiha; Muhammad Raihan Alfarizi; Dela Dwi Oktalena (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
This research aims to explore how sociology contributes to shaping student character by understanding how social, cultural and historical components influence character development. It also explores the impact of applying educational sociology in character education to help students identify social problems that influence their character formation. This research uses qualitative research, with a focus on journal analysis to investigate the role of sociology in shaping student character at school, where data is taken through articles, books and journals to collect relevant information about the application of sociology in character education, emphasizing the importance of understanding social structure, dynamics, and problems in forming individual character. The results of this research underline the important role of sociology in guiding students' attitudes and behavior towards character formation in educational settings, which aims to cultivate individuals with strong moral values and responsible citizenship.